Green fodder cultivation improves technical efficiency of dairy farmers in semi-arid tropics of central India: a micro-analysis. Issue 4 (1st December 2022) - Choudhary, Bishwa Bhaskar; Sharma, Purushottam; Singh, Priyanka; Kumar, Sunil; Gupta, Gaurendra; Kantwa, S. R.; Upadhyay, Deepak; Wasnik, Vinod Kumar; Prasad, Mahendra; Sharma, R. K.
Abstract: This study assessed the impact of improved green fodder production activities on technical efficiency (TE) of dairy farmers in climate vulnerable landscapes of central India. We estimated stochastic production frontiers, considering potential self-selection bias stemming from both observable and unobservable factors in adoption of fodder interventions at farm level. The empirical results show that TE for treated group ranges from 0.55 to 0.59 and that for control ranges from 0.41 to 0.48, depending on how biases are controlled. Additionally, the efficiency levels of both adopters and non-adopters would be underestimated if the selectivity bias is not appropriately accounted. As the average TE is consistently higher for adopter farmers than the control group, promoting improved fodder cultivation would increase input use efficiency, especially in resource-deprived small holder dairy farmers in the semi-arid tropics.